Numerical Study of the Aerodynamics of a Hovering Hummingbird's Wing with Dynamic Morphing. (21st February 2022) - Dong, Yuanbo; Song, Bifeng; Xue, Dong; Li, Yuanbo; Yang, Wenqing
Abstract : To deepen our understanding of the aerodynamics by which hummingbirds use flexible wings to hover efficiently during flapping flight, a three-dimensional wing model with dynamic morphing was developed according to the morphological and kinematic data of a hovering hummingbird's wing. Navier-Stokes equations were solved on a dynamically deforming grid to study wing aerodynamics. In numerical simulations, boundary-based smoothing and overset methodologies were used in combination to update the interior nodes of cells in the computational domain, allowing those nodes to accommodate the motion of the flexible wall. This study showed that the leading edge vortex (LEV) attached to the wing was stable during the downstroke but extremely unstable and shed continuously during the upstroke. In the results of the downward stroke, the different vortices separated from the surface and formed a vortex ring. The difference is that the leading edge vortex induced a vortex ring near the root and a smaller and weaker vortex ring near the wingtip during the upstroke. A significant enhancement in aerodynamic forces was found during the downstroke, along with a large number of power consumptions. We found that the asymmetry in the time-averaged vertical force between the two half strokes was 3.5, and the value was higher than that reported earlier. Aerodynamic force coefficients and efficiency matched well with those of another hummingbird wing (the ruby-throated hummingbird). It is worth noting that hummingbirds can maintain a similar wingtip speed by flapping their wings, but different strategies are adapted to hover efficiently due to the differences in size and body weight. The results of this study help to better understand the aerodynamics of the hovering hummingbird.